Teacher reform in Indonesia the role of politics and evidence in policy making - Chu-Chang, Mae. (Washington, D.C World Bank, 2014)
One of the noteworthy global achievements of the past two decades has been the remarkable increase in the number of children attending school and the number of children completing the primary cycle. As more children start school, the focus has shifted toward the quality of their education?on true learning, not just schooling. The critical role played by teachers to enhance the quality of education is especially salient in a populous, geographically dispersed, and culturally diverse country such as Indonesia. With close to three million teachers, Indonesia has one of the largest and most diverse cadres of educators in the world. The comprehensive Teacher and Lecturer Law, approved by the Indonesian government in 2005, radically reformed the management and development of those teachers. Teacher Reform in Indonesia: The Role of Politics and Evidence in Policy Making features a comprehensive analysis of the teaching profession and the impact of recent reforms, which included the doubling of a teacher?s basic pay once he/she satisfies the conditions necessary for certification?a factor that has improved the status ofteachers and attracted better candidates to teacher training institutions. This book provides a description of the political and economic context in which the reform was developed and implemented as wellas an analysis of how the reform affected teacher quality and student outcomes. The book?s framework promotes an approach to reforms based on improving the nature of teacher recruitment; preservice education; induction, mentoring, and probation; formal certification; continuing professional development; teacher performance appraisal; and ongoing career development. The recent history of teacher reform in Indonesia can inform other countries seeking to improve their educational systems and, ultimately, the success of their teachers and students. This book should therefore be of particular interest to Ministries of Education that contemplate similar reforms and development agencies and practitioners that seek to support country efforts to strengthen the teaching profession.
Includes bibliographical references and index.
Keywords: Teachers -Government policy -Indonesia.